Bosnia and Belgium: National divisions and party cartels - Simović, Vlade (Politeia, 2017)
This paper is comparative analysis which underlines 'genetics' of divided societies of Bosnia and Herzegovina and Belgium and their national party cartels. The main thesis elaborates that religion, together with binding socio-economic connotations, was basic factor of producing three nations in Bosnia and Herzegovina and was additional factor of their mutual conflicts. In Belgium, on the other side, strengthening of distance between Dutch and French language, between German conservative north and Romance leftist south, was the main factor of shaping strong and confronted identities of Flemish and Walloons. In these divided societies, national elites accomplish dominant role. They accomplish strong partocratic systems and national party cartels which shape all main social and political processes such as in cases of Bosnia and Belgium.